Developmental noise and ecological opportunity across space can release constraints on the evolution of plasticity. Issue 1 (29th July 2019) - Draghi, Jeremy
Abstract: Phenotypic plasticity is a potentially definitive solution to environment heterogeneity, driving biologists to understand why it is not ubiquitous in nature. While costs and constraints may limit the success of plasticity, we are still far from a complete theory of when these limitations actually proscribe adaptive plasticity. Here I use a simple model of plasticity incorporating developmental noise to explore the competitive and evolutionary relationships of specialist and generalist genotypes spreading across a heterogeneous landscape. Results show that plasticity can arise in the context of specialism, preadapting genotypes to later evolve toward plastic generalism. Developmental noise helps a mutant with imperfect plasticity successfully compete against its ancestor, providing an evolutionary path by which subsequent mutations can refine plasticity toward its optimum. These results address how the complex selection pressures across a heterogeneous environment can help evolution find paths around constraints arising from developmental mechanisms. Abstract : Evolution of niche use on the line of descent of an eventual generalist population. Each line represents a single genotype; line widths indicate frequencies & colors are arbitrary. Vertical movement of lines shows migration in space toward resource clusters. HIGHLIGHTS: Developmental noise interacts with environmental heterogeneity to allow phenotypic plasticity to evolve. Plasticity can arise first via exploitation of a novel resource, providing a pathway for the evolution of a plastic, generalist genotype.